Physician Perspectives on Implementation of Real-Time Benefit Tools: A Qualitative Study - Everson, Jordan; Whitmore, Christine C.; Mattingly, T. Joseph, II; Sinaiko, Anna D.; Dusetzina, Stacie B. (Applied Clinical Informatics, 2022)
Objectives Congress and Medicare have required real-time benefit tools (RTBT) to provide patient-specific medication price information during prescribing to decrease the cost of medications. We sought physicians' perspectives on how these tools might most effectively improve their selection of low-cost medication.Methods We conducted 15 semi-structured interviews of physicians (6 oncologists, 1 endocrinologist, 4 rheumatologists, and 4 from internal medicine) and identified key themes across interviews during coding and analysis.Results Although physicians saw value in real-time medication price information, they were wary of the complexity of obtaining specific information and the potential for inaccuracies. Physicians described how medication price information would be used in various prescribing scenarios including from simple substitutions (different drug formulations) to more complex decisions (different drug classes). In more complex situations, physicians were concerned that price information might only be available after discussing options with the patient, which would be too late to inform decisions. Concern about adding more information to the electronic health record was common.Conclusion While most physicians saw value in implementation of RTBTs, they also expressed concerns related to the accuracy of information, the availability of information at the right time in the clinical workflow, and the most effective format for information. Many concerns raised paralleled the “Five Rights of Clinical Decision Support” framework and indicate the need for additional design work to achieve benefit from RTBTs. Beyond the public policy that has supported the availability of RTBTs, substantial development will be required to ensure that information is used to improve prescribing decisions.
Keywords: costs; clinical decision support; qualitative; providers